2014
DOI: 10.1159/000357433
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Treatment of End-Stage Renal Disease in the Elderly

Abstract: The features of ageing complicate the management of end-stage renal disease. These complicate all dialysis modalities and will greatly affect the ability to cope with interventional treatments and quality of life. The presence of other illnesses and comorbidity associated with kidney disease mean that many patients have a poor prognosis. It is therefore important to consider the impact of dialysis on lifestyle and whether survival will actually be improved for frail older patients. This review article consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 157 publications
(93 reference statements)
1
9
0
1
Order By: Relevance
“…Vascular access, intradialytic hypotension, which may relate to myocardial dysfunction, and impaired autonomic function with hemodynamic instability, bleeding and amyloidotic arthropathy represent the most critical aspects of HD treatment. Furthermore, we should consider that PD is a less expensive treatment than HD [52,53]. However, PD patients should be constantly monitored with clinical and instrumental tools, including bioelectrical impedance, CTR and echocardiogram, since they are at increased risk of developing volume overload and cardiovascular disorders [54], as confirmed by the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Vascular access, intradialytic hypotension, which may relate to myocardial dysfunction, and impaired autonomic function with hemodynamic instability, bleeding and amyloidotic arthropathy represent the most critical aspects of HD treatment. Furthermore, we should consider that PD is a less expensive treatment than HD [52,53]. However, PD patients should be constantly monitored with clinical and instrumental tools, including bioelectrical impedance, CTR and echocardiogram, since they are at increased risk of developing volume overload and cardiovascular disorders [54], as confirmed by the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Elderly RT recipients have an increased risk of infections and cardiovascular events than younger patients. 1,24 With aging, the immune system undergoes structural and functional changes, including qualitative alterations in T cell activation and/or quantitative differences in T cell subsets. 25 This results in higher incidence and severity of infectious complications in the elderly compared with younger transplant recipients for the same degree of immunosuppression.…”
Section: Risks Of Rt In the Elderlymentioning
confidence: 99%
“…65 Another very important strategy to increase RT in elderly candidates is to promote living donation. 24 The proportion of LD recipients 65 years or older doubled in the United States from 6.8% in 2001 to 13.7% in 2011. 66 Several studies 10,[91][92][93] showed that LD RT was associated with better graft survival rates than DD RT in elderly recipients, as well as in younger ones.…”
Section: Two Phenotypic Frailty Scalesmentioning
confidence: 99%
“…Today, most of the ESRD patients are older patients, which this naturally increases the number of elderly people in need of hemodialysis treatment (10)(11)(12). This can be due to increased longevity of ESRD patients, high prevalence of diseases such as diabetes and hypertension in the elderlies, as well as the development of technology and health services in recent years (10)(11)(12). Studies reported that the incidence of old age issues such as falling, decreased physical activity, poor nutrition and cognitive disorders in elderly with ESRD are higher than younger patients (13).…”
Section: Introductionmentioning
confidence: 99%